Differences between students' learning behaviors and performances of adopting a competitive game-based item bank practice approach for learning procedural and declarative knowledge. Issue 5 (18th August 2019) - Hwang, Gwo-Haur; Chen, Beyin; Chen, Ru-Shan; Wu, Ting-Ting; Lai, Yu-Ling
ABSTRACT: Competitive game-based learning has been widely discussed in terms of its positive and negative impacts on learners' learning effectiveness and learning behavior. Although different types of games require different kinds of knowledge to accomplish the task via competition, few studies have considered that knowledge types, such as procedural knowledge and declarative knowledge, might play important roles in competitive game-based learning. Also, some studies have found that learners with high prior knowledge gain benefits from playing games, but tend to develop declarative rather than procedural knowledge. To address this problem, the independent sample t-test was used to analyze students' learning effectiveness in order to explore how different knowledge types in a competitive game-based item bank practice system would influence learners. Lag sequential analysis was used to analyze the learners' behavior. The results show that learners with procedural knowledge (web programming) scored significantly lower than those with declarative knowledge (English) on the pre-test. However, the learners with procedural knowledge improved their grades to achieve a similar level to that of students with declarative knowledge on the post-test. The behavior analysis indicated that learners with procedural knowledge tended to review the explanation of the question and re-answer it, and used the competitive game-based item bank practice system more than the learners with declarative knowledge. It is concluded that the competitive game-based item bank practice system had a positive impact on learning effectiveness, especially for learners with procedural knowledge.